A redactional study of the Book of Isaiah 13-23 - Lee, Jongkyung (Oxford Theology and Religion Monographs, 2018)
This book argues that a series of programmatic additions were made to the oracles concerning the nations in Isa 13-23 during the late-exilic period by the same circle of writers who were responsible for Isa 40-55. These additions were made to create continuity between the ancient oracles against the nations from the Isaiah tradition.